The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/2040622316639769
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported functioning in major depressive disorder

Abstract: This study points to the importance of functional outcomes of MDD treatment as well as the need to develop personalized interventions to improve functioning in MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 50 publications
1
35
0
2
Order By: Relevance
“…Functional impairment is a key consequence of major depressive disorder (MDD). 1,2 Multiple domains of functioning are typically impaired in patients with MDD, particularly their ability to work and work productivity. [3][4][5][6][7] Depression has a considerable impact in the workplace worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional impairment is a key consequence of major depressive disorder (MDD). 1,2 Multiple domains of functioning are typically impaired in patients with MDD, particularly their ability to work and work productivity. [3][4][5][6][7] Depression has a considerable impact in the workplace worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Systematic reviews have shown that improvement in mood symptoms is only modestly correlated with functional outcomes in MDD. 13,[15][16][17] Functional impairment can persist in patients with MDD even after remission of mood symptoms, 2,18,19 and residual functional impairment has been associated with an increased risk of relapse and recurrence of depression. 20,21 The clinical relevance of cognitive symptoms, including disturbances in attention, memory, processing speed, and executive functioning, and their role in work-related disability is well documented in MDD.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Compared with the general population, patients with MDD report substantial functional impairment. 3 8 In the Sequenced Treatment Alternatives to Relieve Depression (STAR*D) study, a large US study designed to assess the efficacy of sequential acute treatments for MDD, only 7% of patients reported within-normal functioning before initiation of antidepressant therapy. 8 The level of functional impairment associated with depression has been shown to equal or exceed that associated with other severe chronic general medical conditions, such as diabetes and congestive heart failure.…”
Section: Introductionmentioning
confidence: 99%
“… 14 16 Available data suggest that impaired functioning in patients with MDD can persist even after marked improvement in depressive symptoms. 8 , 14 , 17 19 This is of clinical significance because residual functional impairment has been associated with an increased risk of relapse and recurrence of depression. 20 , 21 From a patient’s perspective, return to usual levels of functioning may be as important a treatment outcome as resolution of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many remitted patients continue to experience ongoing deficits in functioning or quality of life. 11,12 Symptom-based scales will likely remain the standard for treatment outcome assessment in randomised controlled trials and clinical practice. However, it may be worthwhile to develop measures that assesses relevant domains other than symptom resolution.…”
mentioning
confidence: 99%